Teachers’ efficacy beliefs in mathematics teaching: a study of public primary schools in Sarawak / Julaihi, N. H - Julaihi, Nor Hazizah (Universiti Teknologi MARA Cawangan Sarawak, 2020)
The Ministry of Education in Malaysia has voiced concern over the serious problems of underachieving primary school students in Mathematics. While the Ministry is gearing its education direction towards a new generation of STEM experts, the teachers have been assigned to shoulder the movement of the vision. Hence, their views must be understood. A study was conducted among 66 Mathematics teachers from 39 public primary schools in the sub-urban district of Samarahan in Malaysia to understand their mathematics teaching efficacy. The Mathematics Teaching Efficacy Beliefs Instrument (MTEBI) by Enochs, Smith and Huinker (2000) was adapted and used in the data collection. Quantitative data analysis methods include descriptive statistics and the analysis of variance. The results indicated that the teachers were confident of their efficacy in Mathematics teaching. Specifically, the teachers’ personal efficacy was slightly lower than outcome expectancy. In addition, there was a moderate positive significant relationship between teachers’ personal efficacy and outcome expectancy. Gender, years of Mathematics teaching experience and highest education attained were not significant to teachers’ efficacy